Analisis Proksimat Amoniasi Jerami Padi Dengan Penambahan Isi Rumen - Zuraida Hanum; Yunasri Usman (Agricultural Faculty, 2011)
The proximate analysis of ammoniated rice straw added with rumen contentABSTRACT. A study about proximate analysis on ammoniated rice straw that added with rumen content was conducted at Agricultural Faculty, Syiah Kuala University. Field research was done at Experimental Farm Animal Husbandry Department, followed by proximate analysis done in the Animal Feed Laboratory. Factorial completely randomizes design with four replications was applied in this research. Storage time (4 Level) was the first factor analyzed, and the second one was the rumen content level (4 level). Analysis of variance was used to determine the differences among treatments. When it occurred, it followed by working on the Duncan Multiple Test to find the difference of each treatment. Data record were taken from the percentages of dry matter, crude fiber, crude protein, crude lipid, and ash. Rice straw and rumen content were analyzed before treatments were applied. The study result indicated that the storage times of ammoniated rice straw that were given rumen content decreased the percentage of crude fiber and dry matter in highly significant different (P0.01). On the other hand, the percentage of ash and crude protein were increased also in highly significant difference (P0.01). Meanwhile, the percentage of crude lipid due to both storage time and rumen content added factors showed highly significant different (P0.01). The storage time up to fourth week, and adding of 25 % rumen content to ammoniated rice straw, can increase it nutritive value. It was concluded that generally the quality of product resulted from this research was very good. Therefore it is acceptable to provide to animals.